Econometric analysis of integration of selected new eu member cee stock markets with global stock market and eurozone: Impact of global financial crisis - Jan Sucháček; Jaroslav Koutský; Lorena Caridad y López del Río; Petr Sed'a (Amfiteatru Economic Journal, 2021)
The period of the global financial crisis can be characterized by the spillover of negative innovations among stock markets worldwide. Stock markets in Central Europe were not excluded as they are not isolated from global stock markets. Recently published scientific studies dealing with this theme were mainly focused on the integration of the new EU members' stock markets with the eurozone only. Hence, this paper aims to investigate, compare and interpret integration among stock markets of selected new EU member states in Central Europe (the Czech Republic, Hungary, and Poland), the global stock market and the eurozone equity market within 2004-2018. The added value of this article consists especially in using a wider spectrum of econometric tools (cointegration, VAR model, Granger causality, variance decomposition) and comparison of changes of mutual relationships in three different testing sub-periods to study the dynamics in time. Our research is accomplished via usage of data on daily frequency. Delivered results showed that the degree of integration of Central European stock markets with the US stock market and eurozone significantly increased during global financial crisis. Moreover, stock markets in Central Europe are more integrated with the global stock market than the euro area.
Keywords: F36; G15; G31; 330; global financial crisis; Granger causality; integration; stock market; VAR model; variance decomposition